DEVELOPMENT OF CACAO VARIETY IDENTIFICATION METHOD USING COMBINATION OF FTIR SPEKTROSCOPY AND MULTIVARIATE ANALYSIS - Semuel Simra; Tarso Rudiana (Jurnal Crystal : Publikasi Penelitian Kimia dan Terapannya, 2023)
Abstract Indonesia is the third largest cocoa producing country after Ivory Coast and Ghana. Indonesian cocoa agribusiness still faces obstacles, among others, the low quality of cocoa beans caused by different types of cocoa plant varieties. The amount of phenolic compounds in cocoa depends on the variety. There are 3 variety of cocoa plants, namely Criollo (fine flavoured cocoa) Forestero (bulk cocoa) and Trinitario (Criollo and Forestero hybrids). This study aims to identify cocoa varieties quickly and efficiently to control the quality of cocoa bean production. The method used in this study is a combination of Fourier Transform Infrared (FTIR) Spectroscopy Method and Multivariate Analysis Method. The combination of these two methods has been widely developed for the identification and authentication of types of plants that have similar or close ties. Based on the results of FTIR (Fourier Transform Infrared) analysis at a wave number of 4000-400 cm-1 to 15 samples of cocoa beans, a spectrum that is multicomponent and relatively the same is obtained. The spectrum data is processed by the multivariate analysis method, Principle Component Analysis (PCA) and obtained that the 3 variety of cocoa can be clearly distinguished where the value of the main components (PC-1 and PC-2) is 92.03%.